Pros and Cons of Computer Technologies in Education - Sidiknazarova Zulfiya Mirsharapovna; Shamuratova Malika Shadjalilovna; Amanov Alisher Kakhramonovich; Kiyasova Ra’no Malikovna (Zien Journals, 2022)
At the outset, we note that computer technology (CT), the use of information and communication technology (ICT), computer-assisted learning (CT), multimedia technology learning (MT) and similar concepts have been taken for granted in education in recent decades. Increasingly, they are used by teachers, as well as students directly in teaching or individual (independent) student learning
Keywords: Computer technology; multimedia technology learning